KEPEMIMPINAN DISTRIBUSI DALAM ERA DIGITAL DI SEKOLAH: KOLABORASI, TANGGUNG JAWAB BERSAMA, DAN TANTANGAN IMPLEMENTASI - Faisal; Arismunandar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education in Indonesia faces major challenges in adapting to technological changes and the demands of the digital era. Traditional leadership models that rely on a single school leader are now considered less effective in managing the complexity of this fast-paced era. Distributed leadership has become a relevant model, where responsibilities and decision-making are not centralized in one individual but shared among principals, teachers, staff, and even students. Through a literature review, this article aims to provide an in-depth understanding of the implementation of distributed leadership in the context of digital-era schooling. The main discussion includes how collaboration and shared responsibility strengthen learning processes and school management, as well as the challenges faced in implementing distributed leadership amid digital transformation, such as infrastructure readiness, teachers’ digital competence, and shifts in school culture. The conclusion indicates that despite significant challenges, technology-driven distributed leadership has the potential to create more collaborative, innovative schools that are better prepared to face digital-era demands.